2010
DOI: 10.1007/s13148-010-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation markers of poor outcome in laryngeal cancer

Abstract: This study examined molecular (DNA hypermethylation), clinical, histopathological, demographical, smoking, and alcohol variables to assess diagnosis (early versus late stage) and prognosis (survival) outcomes in a retrospective primary laryngeal squamous cell carcinoma (LSCC) cohort. The study cohort of 79 primary LSCC was drawn from a multi-ethnic (37% African American), primary care patient population, diagnosed by surgical biopsies in the Henry Ford Health System from 1991 to 2004 and followed from 5 to 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
1
26
1
1
Order By: Relevance
“…HIC1 was found to be methylated in 5 of a total of 79 cases. Stephen et al (33) revealed that the hypermethylation of HIC1 may be an independent predictor of poor survival in laryngeal carcinoma. Patients with laryngeal cancer and HIC1 methylation had a median survival time of 1.02 years, as compared to the median survival time of 4.40 years of patients without HIC1 methylation.…”
Section: Discussionmentioning
confidence: 99%
“…HIC1 was found to be methylated in 5 of a total of 79 cases. Stephen et al (33) revealed that the hypermethylation of HIC1 may be an independent predictor of poor survival in laryngeal carcinoma. Patients with laryngeal cancer and HIC1 methylation had a median survival time of 1.02 years, as compared to the median survival time of 4.40 years of patients without HIC1 methylation.…”
Section: Discussionmentioning
confidence: 99%
“…APC inactivation as a result of promoter hypermethylation occurred in 25% of OSCC cell (42). In a primary LSCC cohort of 79 patients, aberrant methylation of APC occurred in 16% of the tumors (43). In our study, aberrant methylation of APC was a common event in both primary tumors supporting methylation of APC as an early event in LSCC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter hypermethylation of RARβ and APC in both early and late stage tumors and of CHFR in only late stage tumors appear to suggest an epigenetic progression continuum, with CHFR as a late event and a putative diagnostic biomarker for late stage disease[43]. In another study of 79 primary laryngeal squamous cell carcinoma, aberrant methylation of ESR1 and HIC1 signified independent markers of poorer outcome[89]. …”
Section: Delineating An Epigenetic Continuum In Hnsccmentioning
confidence: 99%